Effect of shades on growth, yield and quality of cherry tomato in Indonesia - M. ABROR; YOGI SUGITO; NURUL AINI; AGUS SURYANTO (Journal of Agrometeorology)
This study aimed to assess the effect of shade treatments on growth, yield, and fruit quality in two tomato varieties (cherry ruby and cherry sweet ruby). Treatments included the use of UV plastic shade, as well as its combination + 25% and 50% paranet. Parameters observed included light intensity, temperature, growth rate, plant height, number of leaves, leaf area, number of fruits, fruit weight, vitamin C content, and sweetness (Brix). Results showed that the addition of paranet significantly reduced light intensity and stabilised temperature, which had a positive impact on growth and vitamin C content but reduced sweetness. The cherry ruby variety showed superior performance in vegetative growth, fruit number and weight, and vitamin C content, while cherry sweet ruby excelled in sweetness. The combination of UV plastic shade + 25% paranet gave the best results in creating a balance between growth, yield, and quality. This study shows the importance of shade management in tomato cultivation in the tropics to optimise productivity and fruit quality.